Continuity of care and outpatient management for patients with and at high risk for cardiovascular disease during the COVID-19 pandemic: A scientific statement from the American Society for Preventive Cardiology - Amit Khera; Seth J. Baum; Ty J. Gluckman; Martha Gulati; Seth S. Martin; Erin D. Michos; Ann Marie Navar; Pam R. Taub; Peter P. Toth; Salim S. Virani; Nathan D. Wong; Michael D. Shapiro (Elsevier, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has consumed our healthcare system, with immediate resource focus on the management of high numbers of critically ill patients. Those that fare poorly with COVID-19 infection more commonly have cardiovascular disease (CVD), hypertension and diabetes. There are also several other conditions that raise concern for the welfare of patients with and at high risk for CVD during this pandemic. Traditional ambulatory care is disrupted and many patients are delaying or deferring necessary care, including preventive care. New impediments to medication access and adherence have arisen. Social distancing measures can increase social isolation and alter physical activity and nutrition patterns. Virtually all facility based cardiac rehabilitation programs have temporarily closed. If not promptly addressed, these changes may result in delayed waves of vulnerable patients presenting for urgent and preventable CVD events.Here, we provide several recommendations to mitigate the adverse effects of these disruptions in outpatient care. Angiotensin converting enzyme inhibitors and angiotensin receptor blockers should be continued in patients already taking these medications. Where possible, it is strongly preferred to continue visits via telehealth, and patients should be counselled about promptly reporting new symptoms. Barriers to medication access should be reviewed with patients at every contact, with implementation of strategies to ensure ongoing provision of medications. Team-based care should be leveraged to enhance the continuity of care and adherence to lifestyle recommendations. Patient encounters should include discussion of safe physical activity options and access to healthy food choices. Implementation of adaptive strategies for cardiac rehabilitation is recommended, including home based cardiac rehab, to ensure continuity of this essential service. While the practical implementation of these strategies will vary by local situation, there are a broad range of strategies available to ensure ongoing continuity of care and health preservation for those at higher risk of CVD during the COVID-19 pandemic.